1994
DOI: 10.1177/104438949407500501
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Conceptions of Family Development over the Life Course

Abstract: Life-cycle models assume universal, fixed, sequential stages of individual and family development and thus ignore the diversity of people, social and physical environments, and culture. The author proposes a new, interdisciplinary life-course model of development based on the concept of nonuniform pathways of development. This model incorporates new family forms, human diversity (race, ethnicity, culture, gender, sexual orientation, and physical/mental states), and environmental diversity (economic, political,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
2

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 15 publications
0
12
0
2
Order By: Relevance
“…This study supports models of human development that are responsive to individual and cultural variations of the life course, unpredictability of life events, capacity for personal choice and creativity, issues of disability, and crisis, resiliency, and transformative possibilities inherent in adversity (Germain, 1991(Germain, & 1994. As this study and the literature review indicated, one needs to add the possibility of transpersonal experiences, including spiritual crises and breakthroughs, and the capacity of some people to achieve spiritual growth through creative engagement with adversity.…”
Section: Death As a Continuation Of Lifementioning
confidence: 80%
“…This study supports models of human development that are responsive to individual and cultural variations of the life course, unpredictability of life events, capacity for personal choice and creativity, issues of disability, and crisis, resiliency, and transformative possibilities inherent in adversity (Germain, 1991(Germain, & 1994. As this study and the literature review indicated, one needs to add the possibility of transpersonal experiences, including spiritual crises and breakthroughs, and the capacity of some people to achieve spiritual growth through creative engagement with adversity.…”
Section: Death As a Continuation Of Lifementioning
confidence: 80%
“…Rather than trying to shape concepts of the family from a single mold, policy makers and researchers would be better advised to recognize the high degree of diversity and fluidity in family and household structure (see Bould, 1993;Hernandez, 1993;Liss, 1987;Trost, 1993; for similar arguments; see Crispell, 1991;Germain, 1994;Riche, 1991;Smith, 1992;and Sorrentino, 1990, for discussions of the changes in families in recent decades). Relational ties vary over the life course as one's procreative family forms and one's family of birth disappears, and marriage, divorce, remarriage, fertility, and mortality reshape the size and composition of an adult's procreative family.…”
Section: Diversity and Fluidity Of Family And Household Structurementioning
confidence: 99%
“…Bain's essay (1978) on the family, as social container, provided the theoretical base for the teaching, updated in the light of more recent views of family development (Carter & McGoldrick, 1989;Germain, 1994). His analysis was that the vulnerability of the individual peaked at times of psychosocial transitions.…”
Section: The Coursementioning
confidence: 97%